2007
DOI: 10.2174/157488807781696267
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Human Mesenchymal Stem Cells to Osteogenic Signals and its Impact on Bone Tissue Engineering

Abstract: Bone tissue engineering using human mesenchymal stem cells (hMSCs) is a multidisciplinary field that aims to treat patients with trauma, spinal fusion and large bone defects. Cell-based bone tissue engineering encompasses the isolation of multipotent hMSCs from the bone marrow of the patient, in vitro expansion and seeding onto porous scaffold materials. In vitro pre-differentiation of hMSCs into the osteogenic lineage augments their in vivo bone forming capacity. Differentiation of hMSCs into bone forming ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
42
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 124 publications
7
42
0
Order By: Relevance
“…In previous studies, dexamethasone (dex) and vitamin D3 were used to promote hMSC differentiation in vitro (12). More recent studies include the MAPK pathway (13), Rho kinase (7), Wnt (5), Notch (14), and receptor tyrosine kinases (3).…”
mentioning
confidence: 99%
“…In previous studies, dexamethasone (dex) and vitamin D3 were used to promote hMSC differentiation in vitro (12). More recent studies include the MAPK pathway (13), Rho kinase (7), Wnt (5), Notch (14), and receptor tyrosine kinases (3).…”
mentioning
confidence: 99%
“…Several studies are reported for differentiation of MSCs in-vitro and in-vivo. Reports indicating differentiation of MSCs in vitro in dexamethasone enriched media have been concluded Differentiation into osteo-cell lines and hence participation in bone formation (Bruder et al 1997(Bruder et al , 1998Siddappa et al 2007). Studies suggesting possibilities of MSCs playing pivotal role in regeneration of vascular tissues are said to play a key role in associated therapies such as impotence, disseminated sclerosis and conditions associated with spinal cord injury (Albersen et al 2011;Steffenhagen et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…This kinase will phosphorylate members of the Smad (mothers against decapentaplegic) family of transcription factors which will translocate into the nucleus to activate BMP target genes. This pathway is designated the canonical BMP signalling pathway [Ducy and Karsenty, 2000;Schmierer and Hill, 2007;Siddappa et al, 2007].…”
Section: Introductionmentioning
confidence: 99%